2017
DOI: 10.1002/cssc.201700491
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Effective Catalyst Separation by New CO2‐Induced Switchable Organocatalysts

Abstract: CO -induced switchable tertiary amine-based organocatalysts were investigated for an efficient catalyst and product separation by its different partitioning between an organic and carbonated water phase. In this case study, the switching ability of eight tertiary amine-based catalysts between the organic and water phase by addition or removal of CO was investigated. Here, the catalyst switched both nearly completely (99.9 %) into the aqueous phase by addition of CO and effectively back into the organic phase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…In methanol, which is a protic solvent, we got only lower yields (up to 82% vs. up to 100%) and enantioselectivities (up to 51% ee vs. up to 93% ee). This observation is in agreement with similar cinchona-based organocatalysis [48]. In methanol, hydrogen bonds could form between the solvent and the catalysts/reactants.…”
Section: Resultssupporting
confidence: 91%
“…In methanol, which is a protic solvent, we got only lower yields (up to 82% vs. up to 100%) and enantioselectivities (up to 51% ee vs. up to 93% ee). This observation is in agreement with similar cinchona-based organocatalysis [48]. In methanol, hydrogen bonds could form between the solvent and the catalysts/reactants.…”
Section: Resultssupporting
confidence: 91%
“…A literature review of the performance of various organocatalysed cross aldol reactions of isatin with enolisable ketones suggested that the choice of solvent is crucial to the yield and enantioselectivity of the reaction [29,32,39] . In catalytic processes, solvent properties such as hydrogen‐bond donating ability (proticity or acidity), hydrogen‐bond accepting ability (basicity) and dipolarity (polarity) have been reported to strongly influence the rate and stereochemical outcome [38,40,41] . These properties have been used by several researchers to rationalise and identify ideal solvents for API solubilisation [42,43] and asymmetric reactions [38,40] as bulk properties like dielectric constant, dipole moments etc, often prove ineffective in understanding such correlations [31,44] .…”
Section: Resultsmentioning
confidence: 99%
“…In catalytic processes, solvent properties such as hydrogen‐bond donating ability (proticity or acidity), hydrogen‐bond accepting ability (basicity) and dipolarity (polarity) have been reported to strongly influence the rate and stereochemical outcome [38,40,41] . These properties have been used by several researchers to rationalise and identify ideal solvents for API solubilisation [42,43] and asymmetric reactions [38,40] as bulk properties like dielectric constant, dipole moments etc, often prove ineffective in understanding such correlations [31,44] . We therefore adopted the Kamlet‐Taft solvent parameters as obtained in literature [45] to rationally understand the variation of enantiomeric excess in different reaction media as observed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The catalyst switched both nearly completely (99.9%) into the aqueous phase by addition of CO 2 and effectively back into the organic phase (99.3%) by expelling CO 2 . 40 Another method that can be used to recovery of a catalyst from a reaction, including a light-controlled phase tag to separate homogeneous catalysts that can be switched between a neutral (lipophilic) phase and a charged (lipophobic) phase through the use of a tag-centered photoreaction. 41 The photoreaction results in drastic changes in the polarity and solubility of the catalyst.…”
Section: Introductionmentioning
confidence: 99%